Musa arunachalensis: a new species of Musa section Rhodochlamys (Musaceae) from Arunachal Pradesh, northeastern India - Sreejith, Puravannoor E.; Joe, Alfred; Sabu, Mamiyil (Phytotaxa, 2013)
A wild banana species from West Kameng District, Arunachal Pradesh, northeastern India, belonging to section Rhodochlamys, is newly described as Musa arunachalensis. A detailed description, additional notes, illustration, phenology and photographs are provided.